(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
Determining demagnetizing factor method of two ferromagnetic disks is described. Dependence of two ferrite disks demagnetizing factor from distance between them is investigated by using ferrite disks of type 30SCH9 with diameter 32 mm and thickness 4 mm.